"أثر التناوب الوظيفي على التحفيز الإداري : – دراسة حالة المؤسسة العمومية الاستشفائية بن عمر الجيلاني بالوادي - " - عبد الحفيظ, العمامرة; فيصل, لغدامسي; زين العابدين, لغدامسي; محمد, عوينات (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة الى تسليط الضوء على قياس أثر التناوب الوظيفي على التحفيز الإداري بالمؤسسة العمومية الاستشفائية بن عمر الجيلاني بالوادي ، يساهم التناوب الوظيفي في زيادة التحفيز لدى الموظفين من خلال توفير فرص للتعلم والتنمية الشخصية ، عندما يتعرض الموظفون لتجارب وظيفية متنوعة، يشعرون بالحماس والتحفيز للتحدي الجديد والتعامل مع مهام مختلفة ، التحفيز الذي ينشأ من التناوب الوظيفي يؤدي إلى زيادة الانخراط والالتزام بالعمل وتعزيز أداء الموظفين ، بالإضافة إلى ذلك، يسهم التناوب الوظيفي في تعزيز مشاركة الموظفين ورضاهم الوظيفي، حيث يمكنهم استكشاف قدراتهم وتطوير مهاراتهم في سياقات عمل مختلفة. بشكل عام، يمكن القول إن التناوب الوظيفي يعد استراتيجية فعالة لتعزيز التحفيز الإداري وتحقيق النجاح المؤسسي .This study aims to highlight the impact of job rotation on administrative stimulation at Ben Omar Al-Jilani Hospital in el oued. Job rotation contributes to increased employee motivation by providing opportunities for learning and personal development. When employees are exposed to diverse job experiences, they feel enthusiasm and motivation for new challenges and handling different tasks. The motivation arising from job rotation leads to increased engagement, commitment to work, and enhanced employee performance. Additionally, job rotation contributes to enhancing employee involvement and job satisfaction, as they can explore their capabilities and develop their skills in different work contexts. In general, job rotation is an effective strategy for promoting administrative stimulation and achieving organizational success.
Keywords: التناوب الوظيفي , التحفيز الإداري، المؤسسة العمومية الاستشفائية بن عمر الجيلاني بالوادي; job rotation, administrative stimulation, Ben Omar Al-Jilani Hospital, el oued